A university course in English grammar - Downing, Angela (Redwood, 1992)
Basic concepts, The skeleton the message, The development of the message, Expressing patterns of exprience, Interaction between speaker and hearer, Organising the message, Expanding and projecting the message, talking about events, Viewpoits on events, Talking about 'things' , talking about attributes....